PEMETAAN PERGERAKAN MASYARAKAT KABUPATEN ROKAN HULU PROVINSI RIAU DENGAN SISTEM INFORMASI GEOGRAFIS (SIG) - fitra Ramdhani (LPPM Universitas Abdurrab, 2019)
Rokan Hulu is a regency from region expansion of Kampar Regency with Pasir Pangaraian as a capital of regency, Riau Province. Transportation Development in this area should be able to support distribution and dissemination of regional development. The need for movement always creates of problems, especially when people want to move for same purpose in certain area at the same time. This research aims to determine the magnitude of estimated distribution movement in Rokan Hulu by knowing movement pattern using synthetic method (spatial interaction) called gravity model (GR) in Destination Origin Matrices (MAT) and desire line with Geographic Information Systems (GIS). Movement Distribution is performed with dividing Rokan Hulu into 16 zones. Movement analysis distribution using Gravity Model with trip generation and trip attraction (PACGR).The largest distribution of movement in Rokan Hulu is 75% based on internal movement and 25% based on inter-zone movement. The largest Distribution of inter-zone movement that occurred in Pendalian IV Koto District which has purpose of movement to Rokan IV Koto District. The largest distribution of movement occurred for Rambah Samo, Kunto Darussalam and Pagaran Tapah District has purpose of movement to Ujung Batu District. This is because Ujung Batu District is center of industry and commerce in Rokan Hulu.